The Emerging Role of MR Urography in Imaging Megaureters in Children - Świȩtoń, Dominik; Grzywińska, Małgorzata; Czarniak, Piotr; Gołȩbiewski, Andrzej; Durawa, Agata; Teodorczyk, Jacek; Kaszubowski, Mariusz; Piskunowicz, Maciej (Frontiers in Pediatrics, 2022)
Introduction Megaureter, described as ureter dilatation over 7 mm in diameter, commonly associated with other anomalies, is still a diagnostic and therapeutic challenge. Magnetic Resonance Urography (MRU) appears as a promising method in urinary tract imaging, providing both anatomical and functional information. There are several postprocessing tools to assess the renal function (including differential renal function) and severity of ureteral obstruction based on MRU. Still, the place of this method in the diagnostic algorithm of ureteropelvicalyceal dilatation with megaureter remains underestimated. Analysis of imaging findings in a group of children diagnosed with megaureter was done. Material and methods A retrospective analysis of magnetic resonance urography (MRU) was performed in 142 consecutive patients examined from Jan 2013 to Sept 2019. 25 patients meeting criteria of megaureter (dilatation over 7 mm) in MRU were included in the further analysis. The MRU, ultrasound and scintigraphy results were compared and analyzed together and compared with clinical data. Results The sensitivity and specificity of US was comparable to the MRU in the assessment of upper urinary tract morphology (p>0,05). In 5 out of 25 children megaureter was found in each kidney, in a single case both poles of a duplex kidney were affected. In the diagnosis of ureter ectopia, the MRU was superior to the US which sensitivity did not exceed 16%. The US showed limited value in the diagnostics of segmental ureter dysplasia as a cause of primary megaureter when compared to MRU. Four cases were visualized in MRU studies, while the US examination was negative (all confirmed during surgery). There was a moderate correlation between relative renal function between fMRU and scintigraphy (t=0.721, p=0.477) and in the severity of obstruction assessment between both methods (r=0.441, p<0.05). However in 10 kidneys with megaureter the results in scintigraphy were inconclusive due to signal from megaureter imposing on renal field. Conclusions MRU seems to be a preferred method in the diagnostic algorithm for megaureter, providing both anatomical and functional information. MRU is superior to ultrasonography and scintigraphy in diagnosing urinary tract anomalies with megaureter.